Effects of Organic Matter on Soil Erosion and Runoff Peanuts and Green Pea in Cultivation - Sukandi Sukataatmaja; Yohei Sato; Eiji Yamaji; Masaya Ishikawa (PERTETA, 2002)
Organic matter from manure are used not only for fertilizer but also can be used for preventing soil erosion and runoff. How to manage manure to soil for peanut and green pea CUltivation is especially important, because most farmers plant these crops. The objective of this research is to identify effect of: 1) organicmatter from chicken manure, cow manure and sheep manure on soil erosion and runoff in peanuts and green pea cultivations, 2) mulch from paddy, corn and leaf of banana on soil erosion and runoff. The design is divided into three experiments. First, field experiment for land preparation with treatment plowing with harrowing. Second, field experiment for peanuts and green pea crops with treatment chicken, cow and sheep manure. Third, laboratory experiment for mulching uses treatment with cover percentage of mulch from paddy, corn and leaf of banana. Land preparation using chicken manure decreased soil bulk density and increased soil porosity and aggregate stability index. Lower soil erosion and runoff is attained when treated with chicken manure. Productivity of peanuts and green pea are increased with the increase of manure. Using mulch of paddy, soil erosion and runoff are lower compared with using mulch of corn and leaf of banana.